The Impact of New Technologies in the Environment - Tsoromokos, Nikolaos; Stefanou, Eva; Kritikos, Panagiotis (HAPSc Policy Briefs Series, 2024)
The impact of technology is present in every aspect of the world, including the environment and the people. New and emerging technologies have been invented, in an attempt to solve worldwide problems such as air and water pollution. Are those technologies really making a difference or is the problem enlarging? Questions like these are answered in this policy brief, focusing on solar energy, electric vehicles trying to rule the car industry, and hydrogen technology which leads the way for a much safer and environmentally friendly future. Even though there are drawbacks to every technology, the numerous efforts for a greener environment and new inventions, beneficial to new technologies are present. In this brief, a discussion on the benefits and drawbacks of these technologies is made, and best practices and are discussed to strengthen the benefits and manage any adverse effects.